(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to analyze the role of healthy nutritional standards in improving food quality, a field study conducted on hotels in the city of Tripoli. The study focused on healthy nutritional standards as the independent variable, while the dependent variable was the improvement of food quality. The study sample was a simple random sample, with a target sample size of 63 individuals. A questionnaire was used as the primary tool for collecting data on the study’s variables. Out of the questionnaires, 60 were subjected to statistical analysis using the Statistical Package for the Social Sciences (SPSS), after excluding three questionnaires due to incomplete responses. The study employed a descriptive analytical approach to analyze and interpret the relationship between the study’s variables. The study reached several findings, the most significant of which was the existence of a statistically significant relationship between healthy nutritional standards and the improvement of food quality. The study also provided several recommendations, the most important being the enhancement of nutritional value by increasing ingredients rich in vitamins and minerals and diversifying them.